Between Delft and Stockholm - Brady Burroughs; Katatrina Bonnevier; Hélène Frichot; Katja Grillner (Footprint)
Over the years, colleagues at the Architecture School of Stockholm have developed a most remarkable and inspiring approach to architecture and writing in terms of performances and the performative while integrating feminist and queer theory. Of particular interest are the Critical Studies in Architecture group, the group Fatale for feminist architecture theory and practice, and the Mycket collaboration. By way of an interview between Footprint editors Dirk van den Heuvel and Robert Gorny, and the Stockholm colleagues Brady Burroughs, Katarina Bonnevier, Katja Grillner, and Hélène Frichot questions of pedagogy, research and methodology are further investigated, how to ‘stay with the trouble’ and where to situate newly emerging knowledge models.